Achievements and prospects of global broadband seismographic networks after 30 years of continuous geophysical observations - Ringler, AT; Anthony, RE; Aster, RC; Ammon, CJ; Arrowsmith, S; Benz, H; Ebeling, C; Frassetto, A; Kim, W-Y; Koelemeijer, P; Lekic, V; Lau, H; et al. (American Geophysical Union, 2022)
Global seismographic networks emerged during the late 19th and early 20th centuries, facilitated by seminal international developments in theory, technology, instrumentation, and data exchange. The mid- to late-20th century saw the creation of the World-Wide Standardized Seismographic Network (WWSSN; 1961) and International Deployment of Accelerometers (IDA; 1976), which advanced global geographic coverage as seismometer bandwidth increased greatly allowing for the recording of the Earth’s principal seismic spectrum. The modern era of global observations and rapid data access began during the 1980s, and notably included the inception of the GEOSCOPE initiative (1982) and Global Seismographic Network (GSN; 1988). Through continual improvements, GEOSCOPE and the GSN have realized near-real time recording of ground motion with state-of-art data quality, dynamic range, and timing precision to encompass 180 seismic stations, many in very remote locations. Data from global seismographic networks are increasingly integrated with other geophysical data (e.g., space geodesy, infrasound and interferometric synthetic aperture radar; InSAR). Globally distributed seismic data are critical to resolving crust, mantle, and core structure; illuminating features of the plate tectonic and mantle convection system; rapid characterization of earthquakes; identification of potential tsunamis; global nuclear test verification; and provide sensitive proxies for environmental changes. As the global geosciences community continue to advance understanding of Earth structure and processes controlling elastic wave propagation, global seismographic network infrastructure offers a springboard to realize increasingly multi-instrument geophysical observatories. Here, we review the historical, scientific, and monitoring heritage of global seismographic networks, summarize key discoveries, and discuss future associated opportunities for Earth science.